A major role for P2X1 receptors in the early collagen-evoked intracellular Ca2+ responses of human platelets - Fung, C. Y. Eleanor; Brearley, Charles A.; Farndale, Richard W.; Mahaut-Smith, Martyn P. (Thrombosis and Haemostasis, 2005)
In the platelet, ATP-gated P2X1 receptors have been reported to amplify functional responses to collagen, however the relative importance of early Ca2+ mobilisation events is unknown. We now report that selective desensitisation of P2X1 receptor activity leads to a major reduction in the initial intracellular Ca2+ responses to a wide range of collagen concentrations (0.25–2 μg ml-1). Peak [Ca2+]i increases were reduced to 8.5 and 55% of control, and the maximum rate of rise was reduced to 12 and 33% of control, at low and high collagen concentrations, respectively. This P2X1-dependent acceleration and enhancement of collagen-stimulated Ca2+ responses was not observed in the absence of extracellular Ca2+. These results demonstrate a major role for ATP-gated Ca2+ influx in the early collagen-evoked Ca2+ signals and can at least partly explain the important contribution of P2X1 receptors to arterial thrombosis.
Keywords: P2X1; ATP; collagen; Ca2+; thrombosis